Fanlararo integratsiya asosida boshlang‘ich sinf o‘quvchilarida kreativ faoliyatni rivojlantirish metodikasi - Paluaniyazova, Sapura Kayratdinovna; Hasanova, Dilnura Sardor qizi (SCIENCE and SOCIETY, 2026)
The article analyzes the importance of the primary education system in the development of society, as well as the issues of forming independent thinking, social activity, and creative thinking in students. It also highlights the pedagogical aspects of developing creative activity in primary school pupils, increasing their cognitive interest, and realizing their personal potential.
Keywords: early childhood; creative activity; interdisciplinary integration; teaching methodology; innovative technologies; creative thinking; primary school students; creativity; project; game technologies; reflection